Erk and PI-3 Kinase Are Necessary for Collagen Binding and Actin Reorganization in Corneal Epithelia - Chu, Chia Lin (2000)
PURPOSE: It was recently shown that phosphatidylinositol-(PI)3 kinase is upregulated in wounded rabbit corneal epithelia. Extracellular signal–regulated kinase (erk)-1 and -2 proteins and PI-3 kinase were activated in embryonic corneal epithelia after 1-hour stimulation by type I collagen. In the current investigation specific inhibitors of PI-3 kinase and mitogen-activated kinase-kinase (MEK-1 kinase) were used to determine the role of these signaling molecules in actin reorganization and collagen binding to isolated sheets of corneal epithelial tissue. METHODS: Effects of specific PI-3 kinase and MEK-1 inhibitors (LY294002, PD98059, respectively) were investigated in embryonic corneal epithelial tissues. Avian embryonic corneal epithelia were isolated as tissue sheets, organ cultured in the presence of these specific inhibitors, and stimulated with type I collagen. The tissues were evaluated for collagen-stimulated actin reorganization, erk-1 and -2 and PI-3 kinase activity, total filamentous actin accumulation, and collagen binding. RESULTS: The MEK-1 inhibitor PD98059 decreased erk-1 and -2 phosphorylation and blocked actin reorganization in a dose-dependent manner. The PI-3 kinase 85-kDa subunit was decreased 25% in LY294002-treated tissue, and collagen binding also decreased significantly in tissues treated with MEK-1 and PI-3 kinase inhibitors compared with control tissues. In addition, both inhibitors blocked actin cortical mat reorganization. CONCLUSIONS: PI-3 kinase and erk-1 and -2 signaling pathways are activated and necessary for collagen binding and integrin-mediated actin reorganization in embryonic avian corneal epithelium.